Investigating the Relationship Between Scout as an Extracurricular Activity and Students' Physical Fitness - Supriyadi, Asep; Basri, Hasan; Azhari, Adli; Kusuma, Rizki Ridha (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2024)
The purpose of this study was to analyze the relationship between extracurricular scout as an extracurricular activity and physical fitness of a group of students from YANIIC Jakarta high school. This study used a quantitative research design by applying research method applies quantitative with the type of research an ex-post facto research. The participants of this study are 57 students from YANIIC Jakarta High School. This study used descriptive statistical analysis, analysis requirements test, and final analysis (hypothesis testing) as data analysis techniques. The results showed a moderate level of positive relationship between scout as an extracurricular activity and students' physical fitness. It can be concluded that scout as an extracurricular activity that involves involve physical activities such as walking, hiking, camping, and various field games can bring positive impacts on students' physical fitness. It is because those physical activities can improve physical endurance, muscle strength, and flexibility.